Assessment of durability clad aluminum alloys in asymmetric cyclic loading - Карускевич, М.В.; Погребняк, А.Д.; Маслак, Т.П.; Щепак, С.В. (Proceedings of National Aviation University (archive), 2009)
Comparative efficiency analysis of the two methods of the residual fatigue life estimation under asymmetric cyclical loading has been conducted. It is shown, that the method, based on the determination of the developed on the surface of aluminium alloy D-16AT deformation relief parameters has every reason to compete with known approach, that takes into account indices of asymmetry and uses the diagram of the material’s ultimate state.